Znaczenie Republiki Azerbejdżanu w kontekście bezpieczeństwa energetycznego - Garbaciak, Mateusz (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2015)
The article is about contemporary role of Azerbaijan on the European and Asian countries’ energetic market. The author describes projects and trends connected with economic expansion among Azerbaijani companies. One of them, project of the Southern Energetic Corridor, is the most important for the European Union, because of its energy priorities. The biggest opponent of Azerbaijan is Russian Federation, which is trying to force solutions beneficial only for themselves. Azerbaijani sources of energy are hugely important for the nearest neighbors: Turkey and Georgia. In a few years Azerbaijan could become an energy tycoon and would dictate their own solutions like Russia does today.